Exchange relations on the dark web. Issue 1 (1st January 2017) - Pace, Jonathan
ABSTRACT: This article examines exchange relations on Silk Road, an anonymous online black market formerly located in a concealed portion of the Internet, the dark web. The federal court case of Ross William Ulbricht, Silk Road's architect and executive operator, constitutes the core of my source material, along with Ulbricht's online statements. I argue that Silk Road represented an aggressively capitalist mode of exchange, marked by an absence of state economic regulation, a lack of status codes, an ineffective reputation system, and a resulting deluge of blackmail, scam, coercion, and monopoly. Contrary to its founder's vision of a libertarian utopia, the digital free market in contraband was plagued with fraudulent economic practices, underwritten by a market logic that exploited the site's unique infrastructure. The salient principle of economic relationality on Silk Road was not cooperation and freedom but deception and intimidation.